Has oil richness been a force for income equality in Venezuela over the long term? - Pablo Astorga (European Historical Economics Society (EHES), 2025)
From a long-term perspective little is known about income inequality in Venezuela. This is regrettable as the country offers a unique opportunity to study distributional dynamics in an economy dominated by oil richness since the 1920s amid an accelerated process of structural change amid demographic and institutional transformations. The main reason for this lacuna is scarcity of data. Consistently-defined household surveys are available from 1974 and cover only labour income. The paper benefits from a new set of Ginis based on dynamic social tables with four occupational groups defined by their skill level, and National Accounts data. This evidence sheds light on inequality in two contrasting periods shaped by the interplay of external forces linked to international oil markets and endogenous transformations: one from 1920 to the 1970s of a rapidly growing economy driven by the consolidation of the oil industry, the rise of the middle class, increasing real wages, and industrialisation; the other, ending in 2013 characterised by economic stagnation, a collapse in real wages, the hollowing out of the middle class, declining oil production, volatile oil rents, and de-industrialisation. Altogether, income inequality has been primarily oil driven, first, by a steady rise in oil production and fiscal revenues influencing the pace and nature of endogenous transformations; and, since 1973, by the timing of oil-price shocks. Overall inequality widened during the 1970s and 2000s booms, but also during the slump of the 1980s and 1990s. Prosperity favoured most those in the top group; adversity impacted worst those in the bottom group.
Keywords: J3 O10 O15 Q32 Q43; 330; Economic Development; Income Inequality; Wage Structure; Non-renewable Resources; Oil Prices